Implementing an Ethnomathematics Approach to Enhance Mathematical Connection Skills of Junior High School Students - Marbun, Trivena; Kamid, Kamid; Rohati, Rohati (Universitas Islam Negeri Raden Intan Lampung, 2026)
Ethnomathematics offers a culturally responsive pathway for connecting formal mathematics with students’ lived experiences, yet empirical evidence regarding its effect on mathematical connection skills remains limited. This study examined the effectiveness of an ethnomathematics approach based on Jambi local culture in improving junior high school students’ mathematical connection skills in solid geometry. A quasi-experimental nonequivalent control group design was employed with 64 eighth-grade students from SMP Negeri 1 Muaro Jambi, divided equally into experimental and control groups. The experimental group received culturally contextualized instruction using Jambi cultural objects, whereas the control group followed conventional mathematics teaching. Data were collected through a mathematical connection skills test covering connections among mathematical concepts, between mathematics and other disciplines, and between mathematics and everyday life. Because the posttest data were not normally distributed, group differences were analyzed using the Mann–Whitney U test, followed by effect-size estimation. The experimental group achieved a higher mean posttest score than the control group, 66.88 compared with 33.75, and showed a more favorable distribution of achievement levels. The difference was statistically significant at p < .001, with a large effect size of r = .657. These findings indicate that integrating Jambi local culture into mathematics instruction can substantially strengthen students’ ability to construct, transfer, and apply mathematical relationships. The study positions ethnomathematics as an evidence-based instructional strategy that advances mathematical understanding while reinforcing cultural relevance in secondary mathematics education.